The Wright brothers : how they invented the airplane - Freedman, Russell; Wright, Orville, 1871-1948; Wright, Wilbur, 1867-1912 (New York : Holiday House, 1991)
Follows the lives of the Wright brothers and describes how they developed the first airplane.
Includes bibliographical references (p. 123-124) and index.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), May 1995.
Booklist, December 2005.
Keywords: Wright, Orville, -- 1871-1948 -- Juvenile literature; Wright, Wilbur, -- 1867-1912 -- Juvenile literature; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Aeronautics -- United States -- Biography -- Juvenile literature; Aeronautics -- Biography; Aeronautics -- Biography